2021
DOI: 10.1029/2021jc017381
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Thermohaline Variability on Sea Level Changes in the Southern Ocean

Abstract: The Southern Ocean is responsible for the majority of the global oceanic heat uptake that contributes to global sea level rise. At the same time, ocean temperatures do not change at the same rate in all regions and sea level variability is also affected by changes in salinity. This study investigates 10 years of steric height variability (2008–2017) in the Southern Ocean (30°S to 70°S) by analyzing temperature and salinity variations obtained from the GLORYS‐031 model provided by the European Copernicus Marine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…We found a negative relationship between Chl-a and salinity in the open water province of the Southern Ocean (ANTA: r 0.3). In contrast, we found that the surface salinity is increasing near the Antarctic coast, which was also reported by Chaigneau and Morrow (2002) and Kolbe et al (2021). In the coastal Southern Ocean province the salinity is positively related to Chl-a (APLR: r 0.4), which may be caused by the stronger vertical mixing in these shallower coastal waters and larger brine rejection in the local autumn and winter because of ice cover thinning (Chaigneau and Morrow, 2002;Holland et al, 2006).…”
Section: Polar Biomesupporting
confidence: 73%
“…We found a negative relationship between Chl-a and salinity in the open water province of the Southern Ocean (ANTA: r 0.3). In contrast, we found that the surface salinity is increasing near the Antarctic coast, which was also reported by Chaigneau and Morrow (2002) and Kolbe et al (2021). In the coastal Southern Ocean province the salinity is positively related to Chl-a (APLR: r 0.4), which may be caused by the stronger vertical mixing in these shallower coastal waters and larger brine rejection in the local autumn and winter because of ice cover thinning (Chaigneau and Morrow, 2002;Holland et al, 2006).…”
Section: Polar Biomesupporting
confidence: 73%